Financial Development’s Effect on Economic Growth in Saudi Arabia and the United States: A Comparative Analysis - Lin, Yicheng (Journal of Ecohumanism, 2024)
Over the years, the association existing between the development of the financial institutions and markets along with the economic growth rate for both developed and emerging economies have been extensively researched. A strong financial sector is necessary for an economy to expand and the relationship between these variables are more complex in reality. The goal in this study is to check if the association between the development of the financial sector and the growth rate of per capita income measuring overall economic growth differs across economies that differ in their resource abundance. For this purpose, first, the study has developed a broad and multifaceted index for measuring the level of financial development for one oil exporting economy say Saudi Arabia and one oil importing economy say the United States. In the next step, the study uses time series data between 1970 and 2021 to check for the existing connection between the role of development of financial system in driving growth of the economy separately for the United States and Saudi Arabia. The key findings indicate that first, there is no difference in the average index of financial development in the oil exporting as well as oil importing economies. Second, the relationship between financial development and the growth rate of Saudi Arabia as well as the United States is both weak and insignificant.